Bicycle disc brake thermal performance: combining dynamometer tests, bicycle experiments, and modeling - Feier, I.; Way, J.; Redfield, R. (Proceedings, 2020)
High-power bicycle disc braking can create excessive temperatures and boiling brake fluid, resulting in performance degradation and damage. The goal of this work is to understand brake friction performance and thermal behavior for bicycle disc brakes. A previously described disc braking dynamometer is used to assess brake pad performance of sintered metallic brake pads, organic brake pads, and `power` organic pads in up to 400 W of braking power. The friction coefficient is found to be dependent on both temperature and normal force. Friction curve fits are provided for temperatures between 300 K and 550 K. Organic and `power` organic pads are found to have similar behavior, and have higher friction coefficients compared to metallic pads. Further, brakes on an instrumented bicycle are tested in outdoor field trials during downhill descent. A MATLAB thermal model successfully predicts the downhill field brake disc temperatures when using the friction data curve fits.